Journalism ethics in local newspaper - Moch. Syahri (Masyarakat, Kebudayaan dan Politik, 2020)
Professional and quality journalists are subject to an ethical code and their understanding and competence of said ethics code. Ethics are the minimum values or moral traditions that are used to separate truths from mistakes and good from the bad. Journalism ethics are the rules adhered to by journalists. News coverage has objectives. In order to reach said objectives, journalists should adhere to the professional ethics that they comprehend in the news coverage. Such a comprehension cannot be separated from the different interests involved in the news production process. This research aimed to identify the journalists’ understanding of the values of independence, objectivity, their relationship with their sources and gifts from sources. This research used the phenomenology method. Data collection was done via interviews with 13 Radar Malang journalists. The data analysis employed was Turner’s Theory of Structuration. The research findings presented that first, independence and objectivity are ethical values that are impossible for journalists to maintain. This is since news writing involves interpretation and choices because writing the news is the result of the journalists’ interpretation of their economic interests and journalist idealism. The news is written with a particular tendency in mind. Objectivity is only regarded in the scope of the balance of news. Second, there is a dynamic relationship between journalists and the sources of the news. Journalists are always in a dilemma when writing news that relates to the interests of the news sources. Journalists may receive any gifts from the sources so long as they do not relate to the news. In general, journalists should refuse remittance. However, any other kinds of gifts are still tolerable.